Vital-sign circadian rhythms in patients prior to discharge from an ICU: a retrospective observational analysis of routinely recorded physiological data - Davidson, S; Villarroel, M; Harford, M; Finnegan, E; Jorge, J; Young, D; Watkinson, P; Tarassenko, L (BioMed Central, 2020)
Background: Circadian deregulation in patients treated in an intensive care unit (ICU) is commonplace and is associated with complications such as immune system disruption and delirium. The presence and nature of circadian rhythms in the vital signs recorded in the ICU are not well documented, nor is their generalisability across different ICU populations. This paper investigates the presence of circadian rhythms in the 24 h prior to discharge from an ICU of patients who subsequently recovered. We hypothesise that vital-sign circadian rhythms will be observable in this cohort of patients, that these circadian rhythms will resemble known behaviour in healthy individuals, and that these circadian rhythms will be generalisable across different populations of ICU patients.